Post-COVID-19 Neuropathology and Perspectives of Protective Roles of Estrogens - Rodrigo Portes Ureshino; Roberta Sessa Stilhano; Carla Máximo Prado; Louise Newson (COVID)
Epidemiological data revealed that COVID-19 (Coronavirus disease 2019) is more prevalent and lethal among the elderly population [...]